Protective effects of taurine on learning and memory impairment after exposure to formaldehyde and benzene analogues in young rats - Ting GAO; Yongchao GAO; Zhao YANG; Hui DENG; Zhiyong LIU; Wangwang GUO; Junhong GAO (环境与职业医学, 2023)
BackgroundFormaldehyde and benzene homologues are common environmental pollutants, and their neurotoxicity has aroused widespread concern.ObjectiveTo investigate the effect of taurine on cognitive impairment after exposure to formaldehyde and benzene analogues in young rats.MethodsTwenty four-week old SD rats were randomly divided into four groups, with six rats in each group: control group (clean air), model group (5 mg·m−3 formaldehyde + 5 mg·m−3 benzene + 10 mg·m−3 toluene + 10 mg·m−3 xylene), low-dose taurine intervention group (5 g·L−1 taurine + mixture of formaldehyde and benzene analogues), and high-dose taurine intervention group (10 g·L−1 taurine + formaldehyde and mixture of benzene analogues), and the exposure was administered by oral and nasal aerosol inhalation for 28 d. At the end of exposure, the learning and memory ability of rats in each group was measured by Morris water maze test. After the behavioral test, the rats were anesthetized and neutralized, and the brain tissue was harvested for histopathological and molecular biological tests. The apoptosis rate of neurons in hippocampal CA1 area was detected by Tunel assay, and the expression levels of apoptosis-related proteins such as caspase 3, bax, and bcl-2 in hippocampal tissue were detected by Western blotting.ResultsThe growth and development of rats in each group were good during inhalation. During the Morris water maze experiment, the escape latencies of rats in the taurine intervention groups were not different from that in the control group (P>0.05) from day 3 to day 5 of training, while the escape latency of rats in the model group was significantly higher than that in the control group (P <0.05). The number of crossing platform and the target quadrant residence time in the high-dose taurine intervention group were not different from those in the control group (P>0.05), while the two variables in the model group and low-dose taurine intervention group were significantly lower than those in the control group (P <0.05). The apoptotic rates of neurons in the hippocampal CA1 area of rats in the control group, model group, and low-dose and high-dose taurine intervention groups were 5.11%, 18.87%, 9.39%, and 4.63%, respectively. The apoptotic rate in the model group was higher than those in the control group and low-dose and high-dose taurine intervention groups (P<0.05). The expression levels of caspase 3, bax, and bcl-2 in the hippocampus of rats in the low-dose and high-dose taurine intervention groups showed no difference compared with the control group (P>0.05). The expression levels of caspase 3 and bax in the model group were higher than those in the control group and low-dose or high-dose taurine intervention groups (P<0.05), and the expression levels of bcl-2 was lower (P<0.05).ConclusionThe mixed exposure to formaldehyde and benzene analogues can damage the learning and memory ability of young rats, and increase the apoptosis of neurons in hippocampal CA1 region. Taurine can reverse the damage induced by formaldehyde and benzene analogues.